Immunotherapy-induced granulomatous reaction in patients with melanoma. Issue 4 (22nd June 2022) - Taskaynatan, Halil; Gunenc, Damla; Ön, Sercan; Mizrak, Ali; Samancilar, Ozgur; Karaca, Burcak
Abstract : Immune checkpoint inhibitors (ICIs) represent a new era in stage IV melanoma treatment. These agents are generally well tolerated but have specific side effects. The granulomatous reaction is one of such ICI–related adverse events. In this report, we present the cases of three patients with stage IV melanoma who all developed mediastinal and hilar lymphadenopathy during ICI treatment. While a complete response was observed in one patient, near complete responses were observed in the other two patients. Amid these favorable outcomes, all patients developed mediastinal and hilar lymphadenopathy approximately 6 months after the initiation of immunotherapy. Biopsies were performed to explore the underlying pathology of the lymph nodes, which revealed granulomatous reactions rather than metastases. Hence, immunotherapy was continued in all patients. The development of granulomatous lymphadenitis associated with ICIs may mimic disease recurrence/progression clinically and radiographically. Awareness of such type of adverse event is crucial to decide whether to continue therapy or not.